Historical tendencies in the academic direction process of the Medicine Faculty No. 1 from Santiago de Cuba - Sandra María Casas Gross; Frey Vega Veranes; Leonardo Ramos Hernández (Centro Provincial de Información de Ciencias Médicas, 2021)
The process of academic direction of the Medicine Faculty No. 1 from Santiago de Cuba, had its foundations in the context of Oriente University in 1962. Since its foundation it has been conceived to resize the academy, according to the population health problems. The above-mentioned facilitated to verify, by means of the revision of different publications related to the history of medicine, the lack of studies that  analyze the academic direction in the faculty structure, as integral and integrated process, reason why the present study was carried out aimed at characterizing the tendencies that distinguish the development of the academic direction in the enunciated educational context. In this respect, the foundations that sustain the necessity of its improvement are determined. It was concluded that a pertinent scientific-methodological administration that impacts the Santiago environment is required to satisfy the essential health, climatic and social problems.